2002
DOI: 10.2143/ast.32.2.1028
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Bounds for two Value-at-Risk Functionals

Abstract: Based on the notions of value-at-risk and conditional value-at-risk, we consider two functionals, abbreviated VaR and CVaR, which represent the economic risk capital required to operate a risky business over some time period when only a small probability of loss is tolerated. These functionals are consistent with the risk preferences of profit-seeking (and risk averse) decision makers and preserve the stochastic dominance order (and the stop-loss order). This result is used to bound the VaR and CVaR functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…From Lemma 4.2, as both F L 0,1 and F L 0,1 are invertible, the following identities prevail for the extremum quantiles (see for instance Hürlimann 2002…”
Section: Model Risk For Varmentioning
confidence: 99%
See 1 more Smart Citation
“…From Lemma 4.2, as both F L 0,1 and F L 0,1 are invertible, the following identities prevail for the extremum quantiles (see for instance Hürlimann 2002…”
Section: Model Risk For Varmentioning
confidence: 99%
“…Since the Expected Shortfall is monotone with respect to the stop-loss order (see for instance Bäuerle and Müller (2006)), we look at the extremal distributions for the stop-loss order on the set L 0,1 . Following Hürlimann (2002), we use the fact that the stop-loss transform for a distribution F is defined as: F (y))dy.…”
Section: Model Risk For Expected Shortfallmentioning
confidence: 99%
“…), since Q(x, h) is non-decreasing and convex, the composite function u(Q(x, h)) is also non-decreasing and convex wrt h (Bazaraa et al, 2006 Hu¨rlimann (2002) has shown that CVaR preserves the increasing convex order. Hence, we have the following corollary:…”
Section: Spmentioning
confidence: 99%
“…On the other hand, verification of the order −rl may be a simpler matter-and it yields the same decision! Moreover, if the above engineer (or individual) has a choice between two markets that have different mixtures of aged machines, and if the original machine lifetimes in these markets satisfy (14) [here X and Y , ∈ , are the original machine lifetimes that are mixed in the two markets], then Theorem 4.6 determines which market is preferable.…”
Section: Market Of Used Itemsmentioning
confidence: 99%